1977
DOI: 10.3109/inf.1977.9.issue-2.07
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C as a Preventive Medicine against Common Colds in Children

Abstract: During 7 weeks in the spring of 1973 a double-blind pilot study on 172 children in the age group 8-9 was carried out to test the possible effect of 1000 mg vitamin C daily as a prophylactic agent against common colds. During the autumn of 1973, a main study was carried out on 642 children of the same age. The investigations had the same pattern and lasted for 3 months. Both studies have been processed on the same principles. The results were somewhat divergent but, like previously published studies on children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 21 publications
0
53
0
Order By: Relevance
“…The previous searches were extended by MEDLINE searches to identify newer vitamin C-common cold trials. All placebo-controlled studies using regular vitamin C supplementation with 1 g/day of the vitamin were selected for the present quantitative analysis (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), and the results are shown in Table 1. Regular supplementation refers here to initiating supplementation with healthy people and continuing over the occurring common cold episodes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous searches were extended by MEDLINE searches to identify newer vitamin C-common cold trials. All placebo-controlled studies using regular vitamin C supplementation with 1 g/day of the vitamin were selected for the present quantitative analysis (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), and the results are shown in Table 1. Regular supplementation refers here to initiating supplementation with healthy people and continuing over the occurring common cold episodes.…”
Section: Methodsmentioning
confidence: 99%
“…All studies except one (14) were double-blind. Some of the placebo groups were given 10-70mg/day of vitamin C to ensure that the effects of the larger dose were not due to the alleviation of a true dietary deficiency (25,26,28,30). The Relative Effect on the severity of common cold episodes in the vitamin C groups relative to the placebo groups was calculated for each study as the difference between the outcomes in the vitamin C and placebo group divided by the outcome in the placebo group (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of his minireview, Truswell (25) further claims that "in another five combined trials there appeared to be slight amelioration of symptoms, which was not statistically significant" (10,12,(38)(39)(40). In fact, all of the six studies reported in the five papers cited had found a statistically significant benefit in one of the outcome parameters (Table II).…”
Section: Truswell's 1986 Minireviewmentioning
confidence: 99%
“…Numerous intervention studies have investigated the relationship between vitamin C supplementation and the incidence of common cold episodes. Six, large randomized trials of normally nourished subjects in Western countries, whose supplementation period ranged from 2 to 9 months, revealed no effect of vitamin C on common cold incidence (Anderson et al, 1972;Karlowski et al, 1975;Elwood et al, 1976;Ludvigsson et al, 1977;Pitt and Costrini, 1979;Briggs, 1984). However, studies of specific groups, such as subjects under heavy acute physical stress (Hemila, 1996) or British males with extremely low levels of vitamin C intake (Glazebrook and Thomson, 1942;Charleston and Clegg, 1972;Clegg and Macdonald, 1975;Baird et al, 1979), revealed significant reduction in common cold incidence with vitamin C supplementation.…”
Section: Introductionmentioning
confidence: 99%